Tìm X biết : X: 2/3 +X x3/2 + X = 2
Tìm x, biết:
a) 2-x = 2 ( x - 2 ) 3 ; b) 8 x 3 - 72x = 0;
c) ( x - 1 , 5 ) 6 + 2 ( 1 , 5 - x ) 2 = 0; d) 2 x 3 +3 x 2 +3 + 2x = 0;
e) x 3 - 4x- 14x(x - 2) = 0; g) x 2 (x + 1)- x(x + 1) + x(x - 1) = 0.
Tìm x biết:
a. x3 – 25x = 0 b. 3x(x- 2) – x + 2 = 0
c. x2 – 4x - 5 = 0 d.x3 – x2 + 3x – 3 = 0
e. x3 + 27 + ( x + 3)( x – 9) = 0
a: \(\Leftrightarrow x\left(x-5\right)\left(x+5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=5\\x=-5\end{matrix}\right.\)
tìm x biết a)x(2x-1)-(x-1)2-x2=0
b)(x+2)3-x3-6x2=4
a,x(2x-1)-(x-1)^2-x^2=0
<=>x(2x-1-x)-(x-1)^2=0
<=>x(x-1)-(x-1)^2=0
<=>(x-x+1)(x-1)=0
<=>x-1=0
<=>x=1
b,(x+2)^3-x^3-6x^2=4
<=>x^3+6x^2+12x+8-x^3-6x^2=4
<=>12x+8=4
<=>x=-1/3
tick mik nha
`a)x(2x-1)-(x-1)^2-x^2=0`
`<=>2x^2-x-x^2+2x-1-x^2=0`
`<=>x-1=0`
`<=>x=1`
Vậy `x=1.`
`b)(x+2)^3-x^3-6x^2=4`
`<=>x^3+6x^2+12x+8-x^3-6x^2=4`
`<=>12x+8=4`
`<=>12x=-4`
`<=>x=-1/3`
Vậy `x=-1/3.`
a: Ta có: \(x\left(2x-1\right)-\left(x-1\right)^2-x^2=0\)
\(\Leftrightarrow2x^2-x-x^2+2x-1-x^2=0\)
\(\Leftrightarrow x=1\)
b: Ta có: \(\left(x+2\right)^3-x^3-6x^2=4\)
\(\Leftrightarrow x^3+6x^2+12x+8-x^3-6x^2=4\)
\(\Leftrightarrow12x=-4\)
hay \(x=-\dfrac{1}{3}\)
Tìm x, biết:
a) x – 3 = ( 3 – x ) 2 b) x 3 + 3 2 x 2 + 3 4 x + 1 8 = 1 64 .
Tìm x, biết:
a) 2(5x-8)-3(4x-5) = 4(3x-4) + 11;
b) 2 x ( 6 x - 2 x 2 ) + 3 x 2 ( x - 4 ) = 8;
c) 2 ( x 3 - 1 ) - 2 x 2 ( x + 2 x 4 ) + ( 4 x 5 + 4 ) x = 6;
d)(2x)2(4x-2)-(x3 -8x2) = 15.
a) x = 2 7 b) x = 2.
c) x = 2 d) x = 1.
Viết theo HĐT
a) (x - 1)3
b) (2x + 3y)3
c) x3– 64.
d) 27x3+ 8y3
.
Bài 3. Tìm x, biết:
a) (x – 2)3– x2(x – 6) = 5
b) (x – 1)(x2+ x + 1) – x(x + 2)(x – 2) = 4
c) (x + 2)3– (x + 2) = 0
Bài 4. Tìm x biết (x + 2021)3+ (3x - 2022)3=(4x– 1)3
a) \(\left(x-1\right)^3\)
\(=x^3-3x^2+3x-1\)
b) \(\left(2x-3y\right)^3\)
\(=\left(2x\right)^3-3\left(2x\right)^23y+3.2x\left(3y\right)^3+\left(3y\right)^3\)
\(=8x^3-36x^2y+54xy^2-27y^3\)
Bài 3:
a: Ta có: \(\left(x-2\right)^3-x^2\left(x-6\right)=5\)
\(\Leftrightarrow x^3-6x^2+12x-8-x^3+6x^2=5\)
\(\Leftrightarrow12x=13\)
hay \(x=\dfrac{13}{12}\)
b: Ta có: \(\left(x-1\right)\left(x^2+x+1\right)-x\left(x+2\right)\left(x-2\right)=4\)
\(\Leftrightarrow x^3-1-x^3+4x=4\)
\(\Leftrightarrow4x=5\)
hay \(x=\dfrac{5}{4}\)
tìm x biết a) ( x + 3 )2 - ( 2x + 1 ).( x+3 ) = 0 ; b) x3 - 12x2 + 36x = 0
\(a,\Leftrightarrow\left(x+3\right)\left(x+3-2x-1\right)=0\\ \Leftrightarrow\left(x+3\right)\left(2-x\right)=0\Leftrightarrow\left[{}\begin{matrix}x=-3\\x=2\end{matrix}\right.\\ b,\Leftrightarrow x\left(x^2-12x+36\right)=0\\ \Leftrightarrow x\left(x-6\right)^2=0\Leftrightarrow\left[{}\begin{matrix}x=0\\x=6\end{matrix}\right.\)
a, (x+3)2 - ( 2x + 1 ).( x+3)=0 b, x3-12x2+36x =0
=> (x+3).(x+3-2x-1) => x(x2-12x+36) = 0
=>(x+3).(-x+2) => x(x-6)2 = 0
=> x+3=0 <=> x=-3 => x=0 <=> x=0
-x+2=0 <=> x=-2 x-6= 0 <=> x=6
Tìm x, biết:
a) 3x(x - 1) + x - 1 = 0;
b) (x - 2)( x 2 + 2x + 7) + 2( x 2 - 4) - 5(x - 2) = 0;
c) ( 2 x - 1 ) 2 - 25 = 0;
d) x 3 + 27 + (x + 3)(x - 9) = 0.
a) x = 1; x = - 1 3 b) x = 2.
c) x = 3; x = -2. d) x = -3; x = 0; x = 2.
tìm x biết
a) (x-2)3-x(x+1)(x-1)+6x(x-3)=10
b) (x+1)3-(x-1)3-6(x-1)2= -10
c) x3+3x2+3x+28=0
d) x3-6x2+12x-7=0
\(a,PT\Leftrightarrow x^3-6x^2+12x-8-x^3+x+6x^2-18x-10=0\)
\(\Leftrightarrow-5x-18=0\)
\(\Leftrightarrow x=-\dfrac{18}{5}\)
Vậy ...
\(b,PT\Leftrightarrow x^3+3x^2+3x+1-x^3+3x^2-3x+1-6x^2+12x-6+10=0\)
\(\Leftrightarrow12x+6=0\)
\(\Leftrightarrow x=-\dfrac{1}{2}\)
Vậy ...
\(c,PT\Leftrightarrow\left(x+1\right)^3+3^3=0\)
\(\Leftrightarrow\left(x+1+3\right)\left(x^2+2x+1-3x-3+9\right)=0\)
\(\Leftrightarrow\left(x+4\right)\left(x^2-x+7\right)=0\)
Thấy : \(x^2-\dfrac{2.x.1}{2}+\dfrac{1}{4}+\dfrac{27}{4}=\left(x-\dfrac{1}{2}\right)^2+\dfrac{27}{4}\ge\dfrac{27}{4}>0\)
\(\Rightarrow x+4=0\)
\(\Leftrightarrow x=-4\)
Vậy ...
\(d,PT\Leftrightarrow\left(x-2\right)^3+1^3=0\)
\(\Leftrightarrow\left(x-2+1\right)\left(x^2-4x+4-x+2+1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x^2-5x+7\right)=0\)
Thấy : \(x^2-5x+7=x^2-\dfrac{5.x.2}{2}+\dfrac{25}{4}+\dfrac{3}{4}=\left(x-\dfrac{5}{2}\right)^2+\dfrac{3}{4}\ge\dfrac{3}{4}>0\)
\(\Rightarrow x-1=0\)
\(\Leftrightarrow x=1\)
Vậy ...